Otto Hintze e o Estado Nacional na Historiografia alemã (1888-1931) - Wotkosky, Abner Madeira (2020)
The present dissertation aims to promote an evaluation of the historical narratives of the national States development in Europe, as this was a basic theme of the discipline in the context of scientification and consolidation of nationalistic thinking between the 19th and the middle of the 20th centuries. This analysis departs from the assumption that the current atmosphere of the historiographical field allows for important reflections about the historiographical practice, the theoretical basis of the discipline and the socio-political role it played in the West. German historiography is a subject of particular interest in this regard, especially for the relation of the formation of the historical discipline in Germany and the political questions of the country in a context of emergence of numerous nationalistic historical productions. The example that arises as the subject matter of this dissertation is the work of the historian Otto Hintze, who remained intellectually active between the 1880s and the end of the Weimar Republic in the early 1930s. Hintze’s essays are interesting as a source of analysis on how German historiography approached the National-State issue in different moments. The hypothesis, in this case, is that the First World War represented a fundamental break on his work as a historian, when Hintze’s outlook changed from a Prussian-oriented approach as a paradigm for narrating the forming of the National States to a review of this model, caused by the emergence of a new political order and the rise of a "historiographical malaise" in the post-1918 period.These conclusions could be drawn with an analysis of the essays that were published throughout the historian's career. My main theoretical-methodological references were the debates about the concepts of nation, nationalism and national States as modern phenomena, from the perspective of authors like Benedict Anderson, Reinhart Koselleck and Jurgen Habermas, as well as the tools provided by the History of Historiography, both in the classical perspective of Michel de Certeau and in a perspective that understands this research field as an autonomous field within the historical discipline